ReFerm®: a postbiotic fermented oat gruel composition is reducing mast cell degranulation in the colon of patients with irritable bowel syndrome - Biskou, Olga; Walter, Susanna; Israelsen, Hans; Winberg, Martin E.; Bednarska, Olga; Keita, Åsa V. (Frontiers in Medicine, 2024)
Background: Irritable bowel syndrome (IBS) is a highly prevalent gastrointestinal disorder, that affects approximately 4% of the global population. ReFerm® is a postbiotic product of an oat gruel composition fermentation by Lactobacillus plantarum 299v, that has shown to have beneficial effects on intestinal permeability in IBS. In this study, we investigate the effects of ReFerm® on regulators of intestinal permeability, namely mast cells and enteric glial cells.Thirty patients with moderate to severe IBS were treated with enema containing ReFerm® or placebo twice daily. The patients underwent sigmoidoscopy with biopsies obtained from the distal colon at baseline and after 14 days of treatment with ReFerm® or placebo. The biopsies were fixed, embedded in paraffin, sectioned, and stained using markers for mast cells and enteric glial cells, or cryopreserved, lysed, and analyzed by western blotting for markers of mast cells and enteric glial cells. Results: Treatment with ReFerm®, but not placebo, significantly reduced the mast cell tryptase protein levels in biopsy lysates.ReFerm® treatment did not affect the number of mast cells in the colonic biopsies, however, it significantly reduced mast cell degranulation, which could not be observed in the placebo group. ReFerm® or placebo treatment did not affect total protein levels or the number of enteric glial cells in the tissues. Conclusion: Treatment with ReFerm® significantly reduced total mast cell tryptase levels and degranulation of mast cells in colonic biopsies from patients with IBS.The reduction in mast cell activity is potentially part of the mechanism behind the beneficial effects of ReFerm®, however, further work is needed to assess the molecular mechanisms behind the ReFerm® action in the colon of patients with IBS.